Characterization and development of sugar palm-filled phenolic composites as friction materials - Mohammed, Bushra Rashid (2017)
Sugar palm fiber (SPF) is one of the prospective fibers that can be used to reinforce polymer composites. This study aimed to characterize SPF and evaluate the physical, mechanical, thermal, morphological, and tribological properties of the sugar palm filled phenolic (SPF/PF) composites as friction materials. The work was divided into four stages to achieve the specified objectives. The first stage focused on the characterization of the thermal, physicochemical, and morphological properties of untreated and treated SPF fibers. The fibers were treated with sea water for 30 days, and with 0.5 M alkaline solution (NaOH) for 4 days. The results showed that the thermal stability of the untreated fibers was slightly higher than the treated ones due to the high percentage of silica (SiO2) content in the untreated fibers. It was also observed that the fiber surface became clean and smother after treatments and thus better fiber-matrix adhesion was achieved. The second stage examined the physical (Rockwell hardness, water/oil absorption, density, and void content), mechanical (compressive, impact, and flexural), morphological, and thermal (thermogravimetric and dynamic mechanical analysis) properties of SPF/PF composites. Sugar palm fibers in particle size of about ≤ 150 μm and phenolic resin were used to fabricate the composites by the hot press technique, and with different SPF filler loadings of 0, 10, 20, 30, and 40 % by volume. The results showed that, as the SPF filler increases Rockwell hardness decreased, while the water/oil absorption and density increased. The mechanical properties of the composites were also improved, while the thermal stability decreases. Overall, the results showed that the 30 vol. % SPF/PF composites dominated the best physical and mechanical properties, thus it was used for further investigation in the third and fourth stages of this work. The influence of sea water and alkaline SPF fiber treatments on the properties of the phenolic composite was carried out. Both treatments helped to enhance fiber-matrix bonding and consequently improved the physical and mechanical properties of the treated fiber composites. The untreated fiber composites were found to be slightly more thermally stable than the treated ones. In the fourth stage, the tribology behavior of SPF/PF (30 vol. %) was compared with the neat phenolic composites. The results showed that incorporating SPF in phenolic composites decreases the specific wear rate and the coefficient of friction by 64.1 % and 22.6 %, respectively. Furthermore, the tribology behavior of the untreated and treated fiber composites based on the optimum fiber loading was conducted under room and elevated (250 °C) temperatures. The process parameters such as treatment, load and sliding speed were optimized by using DOE (Factorial technique). The treated fiber composites showed better wear behavior compared to the untreated composites. However, the volume losses of all the composites at elevated temperatures were found to be more than those at room temperatures due to the high sliding friction force. Interestingly, the result revealed that SPF can be used as viable reinforcement material in phenolic composites at room and elevated temperatures. In conclusion, sugar palm fiber can be used as an alternative natural fiber for friction materials such as brake pad composites.